Characteristic Analysis of Lithium Manganese Oxide Cathode Materials for Enhanced Lithium Ion ‎Battery Performance - S, Prabhu; S, Vinod; S, Rudhra; M, Balaji (International Journal of Basic and Applied Sciences, 2025)
In this work, we develop a comprehensive simulation approach to evaluate the performance of lithium-ion batteries ‎using a LiMn₂O₄ (Lithium Manganese Oxide) cathode, aimed at supporting high-power electric vehicle (EV) applications. The ‎framework integrates material selection, electrode design, and cell architecture with coupled electrochemical-thermal modeling. ‎Electrode compositions are explicitly defined and implemented in a 3D equivalent-circuit model (RCRTable3D), further linked ‎to thermal models to capture heat generation and dissipation. Simulations are conducted under realistic EV cycling conditions, ‎using 1 A constant current charge–discharge cycles between 2.5 V and 3.34 V, with 10-minute rest periods at 25 °C under ‎forced convection (100 W/m²·K). This setup replicates typical vehicle operation and thermal management scenarios. Key ‎performance indicators—temperature evolution, voltage profiles, SOC (state of charge) trends, energy throughput, and early ‎aging signs—are analyzed to evaluate design parameter influences. Results demonstrate how integrated modeling can optimize ‎cell performance, refining electrode structures and cycling strategies. Overall, this simulation-based study provides insights for ‎enhancing thermal stability, efficiency, and longevity of LMO-based lithium-ion batteries in high-demand applications‎.